2014
DOI: 10.1371/journal.pgen.1004410
|View full text |Cite
|
Sign up to set email alerts
|

Speciation and Introgression between Mimulus nasutus and Mimulus guttatus

Abstract: Mimulus guttatus and M. nasutus are an evolutionary and ecological model sister species pair differentiated by ecology, mating system, and partial reproductive isolation. Despite extensive research on this system, the history of divergence and differentiation in this sister pair is unclear. We present and analyze a population genomic data set which shows that M. nasutus budded from a central Californian M. guttatus population within the last 200 to 500 thousand years. In this time, the M. nasutus genome has ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

30
316
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(349 citation statements)
references
References 101 publications
(120 reference statements)
30
316
2
1
Order By: Relevance
“…Together with earlier indications in other species (18)(19)(20), our findings show the distribution of minor parent ancestry to be at least in part predictable from genomic features. Knowledge of local recombination should therefore provide a guide to where in the genome minor parent ancestry is expected to be highest.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Together with earlier indications in other species (18)(19)(20), our findings show the distribution of minor parent ancestry to be at least in part predictable from genomic features. Knowledge of local recombination should therefore provide a guide to where in the genome minor parent ancestry is expected to be highest.…”
supporting
confidence: 85%
“…S1) (6,11). Previous studies have reported patterns consistent with these expectations (18)(19)(20) but without investigating ancestry patterns and their relationship to local recombination rates, distinguishing among selection in the parental or hybrid lineages, or determining the major sources of selection in hybrid populations.…”
mentioning
confidence: 83%
“…S1). Previous studies have reported patterns consistent with these expectations (18–20), but without investigating ancestry patterns and their relationship to local recombination rates, or distinguishing among sources of selection.…”
mentioning
confidence: 88%
“…Understanding the distribution of genetic variation on the landscape and the life history or ecological parameters that influence this variation will be important in identifying the taxa most vulnerable to anthropogenic change (Peter and Slatkin, 2013;Brandvain et al, 2014). High levels of heterozygosity have been repeatedly shown to confer resistance to environmental change (Hanski et al, 2006;Willi et al, 2006;Bonin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Even where phenotypic variation is present, measuring genetic variability due to recent divergence can be a problem, particularly in places like California, where speciation and evolutionary diversification have occurred recently (Boykin et al, 2005;Burge et al, 2011). Detection of patterns of recent genetic divergence now can be achieved, however, through the use of markers more suitable for measuring population-level variation, such as microsatellites, restriction site-associated DNA markers (RADseq) (Davey and Blaxter 2010) and whole-genome sequences (Brandvain et al, 2014).…”
Section: Introductionmentioning
confidence: 99%